Shutdown App With Microsoft Agent Animation - lelyana Harahap; Sartika Dewi Purba (Jurnal ICT : Information and Communication Technologies, 2021)
In this study, we will discuss the manufacture ofan application to simplify the use of computers and provide animation effects from Microsoft Agent that can reduce the level of user saturation when shutting down the computer. Microsoft Agent is an animation commonly used in Microsoft Office, especially in Microsoft Word. This Microsoft Agent can provide information about what is happening in the application that we are using. And in the design and manufacture of this application, the Microsoft Agent used provides information that the computer to be used will turn off in a countdown of 10 seconds when pressing the process button according to the instructions from the microsoft agent.